2008
DOI: 10.1080/15569520701712984
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skin and eye irritation of 14 products under the stepwise approach of the OECD

Abstract: The determination of acute eye and skin irritation is included in international regulatory requirements for the testing of chemicals, because of the possibility of exposure during the production, transport, marketing, and disposal of products. Although there have been some advances in the areas of refinement and reduction, no single battery of tests has emerged as being acceptable as a complete replacement for the conventional Draize rabbit eye and skin irritation tests. Currently, dermal irritation and ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…What we know is that azadirachtin has no genotoxic effect on human cells, but may have antiproliferative effects, as evidenced by the changes in the cell cycle of human lymphocytes, some of which also displayed aberrant mitoses and poliploidy with multipolar spindles (208). One study reported that an azadirachtin-based nematicide caused eye irritation but no systemic effects (209). There is also a case report of a 35-year-old woman showing transient signs of neurotoxicity after ingesting azadirachtin in a suicide attempt (210).…”
Section: Neem-based Insecticidesmentioning
confidence: 99%
“…What we know is that azadirachtin has no genotoxic effect on human cells, but may have antiproliferative effects, as evidenced by the changes in the cell cycle of human lymphocytes, some of which also displayed aberrant mitoses and poliploidy with multipolar spindles (208). One study reported that an azadirachtin-based nematicide caused eye irritation but no systemic effects (209). There is also a case report of a 35-year-old woman showing transient signs of neurotoxicity after ingesting azadirachtin in a suicide attempt (210).…”
Section: Neem-based Insecticidesmentioning
confidence: 99%
“…Numerous cosmetics, including mascara, are common causes of ocular irritation, producing mild to vision‐threatening conditions such as blepharitis, contact dermatitis and madarosis . Presently though, reliance on in vivo tests to evaluate such irritation is highly controversial ; there remains substantial dependence on the in vivo rabbit‐based Draize eye test , which since its development 40 years ago has been increasingly criticized for its inherent subjective scoring system, questionable extrapolation to humans, time‐consuming and expensive nature, ability to indicate ocular irritation and ethical acceptability . Criticism of the Draize test further extends to its poor ability to detect effects of mild ocular irritants such as mascara, where results are characterized by high variability and low reproducibility .…”
Section: Introductionmentioning
confidence: 99%